ANALISIS KEBIJAKAN PENGANGKATAN PPPK DALAM PROGRAM MAKAN BERGIZI GRATIS - Zi Lilianda Naufani; Dedy Pribadi Uang (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to examine in depth how the implementation of the policy of attracting PPPK in the MBG program is carried out by the government and analyze the implementation of the policy of attracting PPPK in the MBG program. This study uses a qualitative approach with a literature study type. Data sources in this study were obtained from various relevant literature. The literature used is mainly related to the concept of bureaucratic reform, PPPK policy, public policy implementation, and the Free Nutritional Meals policy program. The data analysis technique in this study uses a qualitative descriptive analysis method. The analysis was carried out through four stages, namely: (1) collection and selection of relevant literature; (2) identification of concepts and key findings from each source; (3) comparison and synthesis of findings between sources; and (4) interpretation with the findings contained in the theoretical framework of George C. Edward III's policy implementation. The policy of featuring PPPK in the Free Nutritional Meals program, especially for SPPG workers, shows an imbalance with honorary workers in other sectors, which has the potential to cause noise and includes political resilience in the government system.